Toxicity and loss of mitochondrial membrane potential induced by Alkyl Gallates in Trypanosoma cruzi - Andréo, Rogério [UNESP]; Regasini, Luís Octávio [UNESP]; Petrônio, Maicon Segala [UNESP]; Chiari-Andréo, Bruna Galdorfini [UNESP]; Tansini, Aline [UNESP]; Silva, Dulce Helena Siqueira da [UNESP]; Cicarelli, Regina Maria Barretto [UNESP] (My University, 2015)
American trypanosomiasis or Chagas disease is a debilitating disease representing an important social problem that affects, approximately, 10 million people in the world. The main aggravating factor of this situation is the lack of an effective drug to treat the different stages of this disease. In this context, the search for trypanocidal substances isolated from plants, synthetic or semi synthetic molecules, is an important strategy. Here, the trypanocidal potential of gallates was assayed in epimastigotes forms of T. cruzi and also, the interference of these substances on the mitochondrial membrane potential of the parasites was assessed, allowing the study of the mechanism of action of the gallates in the T. cruzi organisms. Regarding the preliminary structure-activity relationships, the side chain length of gallates plays crucial role for activity. Nonyl, decyl, undecyl, and dodecyl gallates showed potent antitrypanosomal effect (IC50 from 1.46 to 2.90 μM) in contrast with benznidazole (IC50 = 34.0 μM). Heptyl gallate showed a strong synergistic activity with benznidazole, reducing by 105-fold the IC50 of benznidazole. Loss of mitochondrial membrane potential induced by these esters was revealed. Tetradecyl gallate induced a loss of 53% of the mitochondrial membrane potential, at IC50 value.